Perspectives on Early Power Mobility Training, Motivation, and Social Participation in Young Children with Motor Disabilities - Huang, Hsiang-Han (Frontiers in Psychology, 2018)
The efficacy of traditional training programs (e.g., neurodevelopmental therapy) in promoting independent mobility and early child development across all three International Classification of Functioning, Disability, and Health levels lacks rigorous research support. Therefore, early power mobility training needs to be considered as a feasible intervention for very young children who are unlikely to achieve independent mobility. This perspective article has three aims: (1) to provide empirical evidence of differences in early independent mobility, motivation, daily life activities, and social participation between young children with typical development and motor disabilities; (2) to discuss the contemporary concepts of and approaches to early power mobility training for young children with motor disabilities and the current need for changes to such training; and (3) to provide recommendations for early power mobility training in pediatric rehabilitation. Independent mobility is critical for social participation; therefore, power mobility can be accessible and implemented as early as possible, specifically for infants who are at risk for mobility or developmental delay. To maximize the positive effects of independent mobility on children’s social participation, early power mobility training must consider their levels of functioning, the amount of exploration and contextual factors, including individual and environmental factors.